2018
DOI: 10.1016/j.jip.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, physiological and behavioral responses of honey bee (Apis mellifera) drones to infection with microsporidian parasites

Abstract: Susceptibility to pathogens and parasites often varies between sexes due to differences in life history traits and selective pressures. Nosema apis and Nosema ceranae are damaging intestinal pathogens of European honey bees (Apis mellifera). Nosema pathology has primarily been characterized in female workers where infection is energetically costly and accelerates worker behavioral maturation. Few studies, however, have examined infection costs in male honey bees (drones) to determine if Nosema similarly affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…They are able to infect queens if transferred during mating [59,169], even though they typically are transmitted via the fecal-oral route [170]. Drones infected with N. ceranae exhibit altered flight patterns but are able to maintain spermatozoa viability [171].…”
Section: Seminal Fluid Proteins and Their Potential Roles In Queenmentioning
confidence: 99%
“…They are able to infect queens if transferred during mating [59,169], even though they typically are transmitted via the fecal-oral route [170]. Drones infected with N. ceranae exhibit altered flight patterns but are able to maintain spermatozoa viability [171].…”
Section: Seminal Fluid Proteins and Their Potential Roles In Queenmentioning
confidence: 99%
“…It is commonly accepted that the older forager bees in hives have the highest frequency and most intense infection [45,46,95,96], which is thought to provoke an acceleration of foraging behavior in bees infected by N. ceranae [32][33][34]58,97]. However, given the greater susceptibility of younger worker bees evident in this study, it is possible that various strategies may be employed in the super-organism to reduce contamination by Nosema spp.…”
Section: Discussionmentioning
confidence: 76%
“…For instance, essential oils of E. globolus at 10.0 mg/mL caused an irregular response in bees that were inoculated with DWV-A, although some cases were significant compared to non-inoculated bees. This irregular response could be associated with a saturation of the environment by the volatiles present in the essential oils, generating nonspecific stimulation [52]. It has been proposed that, when faced with a high concentration of stimulus, a nonspecific stimulation can be generated; on the other hand, exposure to low concentrations of the stimulus may not generate a complete stimulation of the antenna [52].…”
Section: Discussionmentioning
confidence: 99%
“…This irregular response could be associated with a saturation of the environment by the volatiles present in the essential oils, generating nonspecific stimulation [52]. It has been proposed that, when faced with a high concentration of stimulus, a nonspecific stimulation can be generated; on the other hand, exposure to low concentrations of the stimulus may not generate a complete stimulation of the antenna [52]. We observed that very low concentrations of the stimulus did not induce olfactory responses, although, exceptionally, 14-day-old bees inoculated with DWV-A and exposed to 0.01 mg/mL of M. piperita essential oil showed a significant decrease in the EAG response; bee age also coincided with a higher DWV-A load (1.0 × 10 11 copy number per bee) detected in the antennas (Figures 2A and 3).…”
Section: Discussionmentioning
confidence: 99%